HUBUNGAN ANTARA KECERDASAN INTELEKTUAL DENGAN PRODUKTIVITAS KERJA PADA MAHASISWA BARU FAKULTAS ILMU SOSIAL DAN HUMANIORA DI UNIVERSITAS “XY” - Devi Jatmika (Universitas Bunda Mulia, 2014)
Senior high school students who continue their education level to the college may face many changes, such as higher academic standards. College students are required to be independent, able to adjust their learning style with college’s tasks. As freshmen who started studying in the college therefore this research aimed to find the relationship between intellectual intelligence and work productivity of freshmen. Intellectual intelligence (IQ) has an important role in one’s ability to learn from experience, obtain knowledge, and adapt with new situations. This research also investigated the influence of intellectual intelligence towards students’ work productivity, in which would predict their study performance in the future. The measurement of IQ was measured by using Culture Fair Intelligence Test (CFIT) and students’ work productivity was predicted by using Kraeplin test. This research method is quantitative study. The subject of this research was freshmen in Social and Science Faculty which are 1094 persons. The total subjects of this research are 779 subjects. The results revealed that there was a relationship between intellectual intelligence (IQ) and work productivity among freshmen. The amount of IQ affect towards work productivity is 10.27% and the rest was affected by another factors. The interaction of intellectual intelligence and other factors, such as students’ persistence, self-efficacy and motivation influence students’ performance for long –term result. Keywords: Intellectual Intelligence (IQ), Work Productivity, Freshmen